ANALISIS EFISIENSI PERSEDIAAN BAHAN BAKU SUSU SAPI MURNI DENGAN MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY PADA SOTO SEDEEP - Maulana, Ardy; Kusumawardhani, Amie (Diponegoro Journal of Management, 2015)
This study was conducted to analyze the efficient inventory level in this case is whole milk using the EOQ (Economic Order Quantity).The object of this research is Restaurant Soto Sedeep that is located in Banyumanik-Semarang. Data obtained based on records maintained by the Soto Sedeep during the period of January to December2014. The data used in this study are: whole milk purchased during 2014, data on whole milk during 2014, ordering cost data, the data storage costs, and also the frequency of purchase. Analyses were performed using the EOQ formula, safety stock, reorder point and maximum inventory in one year.Result of this study indicate thatpolicy of whole milk asone of the raw materials at Soto Sedeep is considered less eficient.Based on EOQ calculation in this study, it is found that as much as 4,074,7 liters whole milk should be ordered in order to have efficient optimum inventor. By applying EOQ, the Soto Sedeep could save about Rp. 10.712,100 of inventory cost over a year period.